Safety of antitumour necrosis factor treatments in chronic rheumatic diseases: therapy discontinuations related to side effects. (June 2016) - Varela, H.; Villamañán, E.; Plasencia, C.; Romero, J. A.; Ruano, M.; Balsa, A.; Herrero, A.
Summary: What is known and objective: The appearance of antitumor necrosis factor drugs (ATDs) has been a major advance in the management of these patients. However, due to the immunosuppressive effect of these therapies, side effects that require treatment discontinuations can appear. The purpose of this study was to evaluate the frequency of ATD discontinuation due to adverse drug effects (ADEs) and the influence of different factors such as diagnosis, ATD prescribed and concomitant disease‐modifying antirheumatic drugs (DMARDs). Methods: Observational study from a prospective cohort conducted in a tertiary hospital (1350 beds) in Spain. Data were obtained from the database of the Rheumatology Outpatient Unit of the hospital and patients' clinical files. Included patients had a diagnosis of RA or peripheral or axial SpA (ankylosing spondylitis, psoriatic SpA, non‐radiographic SpA, SpA associated with inflammatory bowel disease or reactive arthritis) treated between November 2000 and March 2014 with infliximab (IFX), etanercept (ETN) or adalimumab (ADA). Results and discussion: Study cohort included 531 rheumatic patients (282 patients with RA, 53·1%, and 249 patients with SpA, 46·9%). ATDs were discontinued in 62 cases (11·7%) because of ADEs, mainly inmunogenicity and infections (mainly due to infusion reactions, 58·1%, and infections, 19·3%). ATD discontinuation was higher in the group of RA patients compared with SpA (44/282 (15·6%) in RA vs. 18/249 (7·23%) in SpA). The appearance of ADEs that led to drop out was more frequent in patients under IFX therapy (45 (18·6%) with IFX vs. 12 (7·59%) with ETN and 5 (3·81%) with ADA). We observed a significantly increased risk of ADEs when patients received IFX than when ETN or ADA were used ( P  < 0·001); 444 patients (83·6%) received DMARDs in combination with ATDs. The risk of ATD withdrawal was significantly higher in patients treated with leflunomide as compared to those who do not (OR = 1·984, P  < 0·05). What is new and conclusion: Discontinuation of ATD due to ADEs is relatively frequent and it depends on the diagnosis and ATD administered. The risk of treatment discontinuation is higher in patients diagnosed with RA vs. SpA or treated with IFX (rather than with ETN or ADA). The addition of DMARDs to ATDs increased the frequency of treatment discontinuation, up to three concomitant medications. Leflunomide in combination with an ATD significantly increased the probability of treatment discontinuation due to adverse reactions. Abstract : Probability of treatment termination due to an adverse effect in terms of anti‐TNF drug administered.